2022
DOI: 10.1038/s41598-022-17506-3
|View full text |Cite
|
Sign up to set email alerts
|

(+)-Usnic acid and its salts, inhibitors of SARS‐CoV‐2, identified by using in silico methods and in vitro assay

Abstract: The pandemic caused by severe acute respiratory Coronavirus-2 (SARS-CoV-2) has been ongoing for over two years, and treatment for COVID-19, other than monoclonal antibodies, is urgently required. Accordingly, we have investigated the inhibitors of SARS-CoV-2 protein targets by high-throughput virtual screening using a marine natural products database. Considering the calculated molecular properties and availability of the compounds, (+)-usnic acid was selected as a suitable hit. In the in vitro antiviral assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…In a recent study, usnic acid and its salts against SARS-CoV-2 were tested by using in silico methods and in vitro assays [ 79 ]. High-throughput virtual screening using a marine natural product database was used in investigating the inhibitors of SARS-CoV-2 protein targets.…”
Section: Biological Activitymentioning
confidence: 99%
“…In a recent study, usnic acid and its salts against SARS-CoV-2 were tested by using in silico methods and in vitro assays [ 79 ]. High-throughput virtual screening using a marine natural product database was used in investigating the inhibitors of SARS-CoV-2 protein targets.…”
Section: Biological Activitymentioning
confidence: 99%
“…The clinical real-life benefits of HPMC in the nose depend on its efficiency gelling property to trap all particles present in the air [ 8 ]. Indeed, there are studies that explore the opportunity to add other ingredients such as antimicrobial drugs of natural origin to the gelling barrier [ 10 ]. There are natural substances with antiviral effects that could be an interesting starting point for developing a strategy to control the infectious diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are natural substances with antiviral effects that could be an interesting starting point for developing a strategy to control the infectious diseases [ 11 ]. One of these is usnic acid (UA), a dibenzofuran derived from lichen [ 10 ]. UA exists in two enantiomeric forms, depending on the position of the methyl group at the chiral atom, which have no substantial differences in physical properties, but have significant differences in their biological and pharmacological activity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…By binding SARS-CoV-2 Spike protein, UA could contribute to the retention of viral particles into the hydrogel produced by HPMC. UA and remdesivir (a product recently approved for the treatment of COVID-19) showed a similar activity in a SARS-CoV-2 binding assay [ 44 ]. Finally, an in vitro study performed on Vero E6 cells showed a significant activity of UA against three different strains of SARS-CoV-2, namely Wuhan, Delta, and Omicron [ 45 ].…”
Section: Introductionmentioning
confidence: 99%